Internalization of Tasamuh Values Between Religious Communities in Islamic Boarding Schools - Hamidatun Nihayah; Romadlon Habibulah; Syahab S. (Research Journal on Teacher Professional Development, 2024)
Kauman Lasem Islamic Boarding School is in the midst of a community has a various regelion and ethnicities, such as Chinese, Javanese and Arab. The forms of activities carried out in the realm of tasamuh are ta'ziyah, devotional work and other social activities. This has caused researchers to be interested in knowing how the life of tasamuh religious people and the process of internalizing tasamuh values in the students of Kauman Lasem Islamic Boarding School. This research uses a qualitative approach. Data collection is carried out by means of observation techniques, interviews and documentation. Techniques in data analysis include data reduction to filter and simplify data, presentation of data to see the overall picture or certain parts of the study and drawing conclusions to obtain evidence that supports the data collection stage. Based on the research conducted, the following results were obtained: (1) The internalization of tasamuh values between religious people in the students of kauman Lasem Islamic Boarding School is through forms and processes. (2) The supporting factor for the internalization of tasamuh values between religious people in the students of Islamic Boarding School is the location of the cottage in the pecinaan environment. In addition, neighbors who have high social integration are supporting factors in the internalization of tasamuh values between religious people in the students of kauman Lasem Islamic Boarding School, so the inhibiting factor is in the new students, the lack of understanding of the new students towards tasamuh makes them behave as they please.